Unlocking basketball athletic performance: Countermovement Jump Rebound (CMJ-RE) normative reference values derived from force plate data across seven NCAA Division-I Power Five men`s college basketball teams - Berberet, D.; Petway, A.; Bell, K.; Gillen, Z.; Mundy, P.; Barrera, H.; Kabo, J.; Walker, D.; Medenwald, G.; Welsh, B.; McMahon, J. J. (International Journal of Strength and Conditioning, 2025)
Purpose: This study examined the emerging countermovement rebound jump (CMJ-RE) test as an alternative to the drop jump (DJ) to grade reactive strength abilities in elite basketball players. Normative percentile data, rebound jump filter criteria, novel effort metrics, and reliability statistics were analyzed in order to better define the standards for a high-quality CMJ-RE test and to democratize the measurement of reactive jump testing. Methods: 96 NCAA Division-I men`s college basketball players from seven teams performed the CMJ-RE (bounce-method) on bilateral force plates with hands on hips during the 2023-2024 pre-season. Only 87 players met the quality filter criteria for further analysis (three centers, 31 forwards, 53 guards); the center position was not compared in depth due to the limited sample size. Results: Between forwards and guards, positional differences were found for 37% of the 38 reported jump metrics, with guards showing higher rebound jump heights (JH), all other metrics (p < 0.05) favored forwards. Mean ground contact times (GCT) for both positions were >250 ms. On average for both positions, the first jump in the CMJ-RE was completed at 94% JH of a previously collected standalone CMJ JH; and the second jump was completed at 98% JH of the first CMJ-RE JH. Furthermore, percentile ranges (3rd to 97th) accompanied by qualitative descriptors and a traffic light classification system were reported. Conclusion: Overall, the CMJ-RE (bounce-method) is a reliable alternative to the DJ for assessing reactive strength qualities in elite basketball players and may be more sport-specific, due to players frequently performing subsequent jumps rather than one single effort jump. The normative data prepared in this study should serve as a reference point throughout the evaluation of reactive strength for basketball performance coaches and in the return to play process for sports medicine professionals. Those administering the CMJ-RE should use the filter criteria measures outlined in this paper to ensure quality and effort are being met.